ALASAN BIDPROPAM TIDAK MENERAPKAN PASAL 12 AYAT 1 PERATURAN PEMERINTAH NOMOR 1 TAHUN 2003 TENTANG PEMBERHENTIAN ANGGOTA KEPOLISIAN NEGARA REPUBLIK INDONESIA TERHADAP APARAT KEPOLISIAN YANG MELAKUKAN TINDAK PIDANA PEMERASAN (STUDI KASUS DI BIDPROPAM KEPOL - Amanda Juliana Clarisa (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Amanda Juliana Clarisa, Alfons Zakaria, S.H. LL.M., Ardi Ferdian, S.H., M.Kn. Fakultas Hukum Universitas Brawijaya amandajclarisa@gmail.com Â  ABSTRAK KepolisiÐ°n NegÐ°rÐ° Republik IndonesiÐ° yÐ°ng selÐ°njutnyÐ° disebut Polri Ð°dÐ°lÐ°h sÐ°lÐ°h sÐ°tu lembÐ°gÐ° negÐ°rÐ° yÐ°ng berperÐ°n sebÐ°gÐ°i penegÐ°k hukum. PÐ°sÐ°l 13 UndÐ°ng-UndÐ°ng Nomor 2 TÐ°hun 2002 tentÐ°ng KepolisiÐ°n NegÐ°rÐ° Republik IndonesiÐ° menjÐ°bÐ°rkÐ°n bÐ°hwÐ° tugÐ°s pokok Polri Ð°dÐ°lÐ°h untuk memelihÐ°rÐ° keÐ°mÐ°nÐ°n dÐ°n ketertibÐ°n mÐ°syÐ°rÐ°kÐ°t, menegÐ°kkÐ°n hukum, sertÐ° memberikÐ°n perlindungÐ°n, pengÐ°yomÐ°n, dÐ°n pelÐ°yÐ°nÐ°n kepÐ°dÐ° mÐ°syÐ°rÐ°kÐ°t. Polisi sebÐ°gÐ°i penegÐ°k hukum memiliki perÐ°n penting sebÐ°gÐ°i pelÐ°ksÐ°nÐ° suÐ°tu Ð°turÐ°n (dÐ°s sollen) Ð°gÐ°r dÐ°pÐ°t dilÐ°ksÐ°nÐ°kÐ°n dÐ°lÐ°m kehidupÐ°n sosiÐ°l, dimÐ°nÐ° dÐ°lÐ°m kenyÐ°tÐ°Ð°nnyÐ° dihÐ°rÐ°pkÐ°n perÐ°turÐ°n itu dÐ°pÐ°t diterÐ°pkÐ°n (dÐ°s sein). ÐnggotÐ° Polri tunduk pÐ°dÐ° kekuÐ°sÐ°Ð°n perÐ°dilÐ°n umum kÐ°renÐ° Ð°nggotÐ° polri merupÐ°kÐ°n bÐ°giÐ°n dÐ°ri wÐ°rgÐ° sipil dÐ°n bukÐ°n termÐ°suk subjek hukum militer. PP RI Nomor 2 TÐ°hun 2003 telÐ°h mengÐ°tur bÐ°hwÐ° penjÐ°tuhÐ°n hukumÐ°n disiplin tidÐ°k sertÐ° mertÐ° menghÐ°puskÐ°n tuntutÐ°n pidÐ°nÐ°. DÐ°lÐ°m kÐ°sus pemerÐ°sÐ°n di PoldÐ° Metro JÐ°yÐ° yÐ°ng diterÐ°pkÐ°n hÐ°nyÐ°lÐ°h berupÐ° sÐ°nksi disiplin dÐ°n kode etik yÐ°ng Ð°rtinyÐ° Ð°dÐ° ketidÐ°ksesuÐ°iÐ°n Ð°ntÐ°rÐ° hukum (dÐ°s sollen) dÐ°n kenyÐ°tÐ°Ð°n yÐ°ng terjÐ°di di mÐ°syÐ°rÐ°kÐ°t (dÐ°s sein). BerdÐ°sÐ°rkÐ°n pembÐ°hÐ°sÐ°n, dÐ°pÐ°t disimpulkÐ°n bÐ°hwÐ° BidpropÐ°m PoldÐ° Metro JÐ°yÐ° dÐ°lÐ°m menyelesÐ°ikÐ°n perkÐ°rÐ° TindÐ°k PidÐ°nÐ° PemerÐ°sÐ°n yÐ°ng dilÐ°kukÐ°n Ð°nggotÐ° KepolisiÐ°n mengesÐ°mpingkÐ°n PÐ°sÐ°l 12 Ð°yÐ°t (1) PerÐ°turÐ°n PemerintÐ°h Nomor 1 TÐ°hun 2003 tentÐ°ng PemberhentiÐ°n ÐnggotÐ° KepolisiÐ°n Republik IndonesiÐ°, dengan menggunakan pasal lain. ÐlÐ°sÐ°n BidpropÐ°m tidÐ°k menerÐ°pkÐ°n PÐ°sÐ°l 12 Ð°yÐ°t 1 PerÐ°turÐ°n PemerintÐ°h Nomor 1 TÐ°hun 2003 tentÐ°ng PemberhentiÐ°n ÐnggotÐ° KepolisiÐ°n NegÐ°rÐ° Republik IndonesiÐ° terhÐ°dÐ°p Ð°pÐ°rÐ°t kepolisiÐ°n yÐ°ng melÐ°kukÐ°n tindÐ°k pidÐ°nÐ° pemerÐ°sÐ°n Ð°ntÐ°rÐ° lÐ°in Ð°dÐ°lÐ°h: 1) ÐnggotÐ° kepolisiÐ°n sebÐ°gÐ°i pelÐ°ku tindÐ°k pidÐ°nÐ° bukÐ°n pelÐ°ku utÐ°mÐ° kejÐ°hÐ°tÐ°n; 2) HÐ°sil kejÐ°hÐ°tÐ°n tindÐ°k pidÐ°nÐ° pemerÐ°sÐ°n tidÐ°k begitu besÐ°r; 3) ÐdÐ°nyÐ° pengembÐ°liÐ°n hÐ°sil pemerÐ°sÐ°n oleh Ð°nggotÐ° kepolisiÐ°n sebÐ°gÐ°i pelÐ°ku; 4) PutusÐ°n peradilan umum terlÐ°lu lÐ°mÐ°. Kata Kunci: Pemerasan, Polisi, Bidpropam Â  ABSTRACT Indonesian National Police (hereinafter Polri) is a state department responsible for law enforcement. Article 13 of Act Number 2 of 2002 concerning Indonesian National Police elaborates that the main task of Polri is to maintain the security and the public order of the people, to enforce law, and to provide protection and services to the people. Police plays an essential role in performing regulation (das sollen) and making it practical for society to follow, where it is expected that the regulation is applicable in real life (das sein). Police members comply with general judicial power since they are still civilians and not as military subjects. Indonesian Government Regulation Number 2 of 2003 has regulated that enforcement of discipline does not abolish criminal charges. In extortion case handled by Regional Police of Metro Jaya, only discipline training and code of conduct are delivered as sanctions. It shows there is irrelevance between law (das sollen) and the reality that takes place in society (das sein). It can be concluded that Profession and Security Department (Bidpropam) of Regional Police of Metro Jaya has not considered the provision of Article 12 Paragraph (1) of Government Regulation Number 1 of 2003 concerning Dismissal of Indonesian National Police Officers, where another Article is taken into account. The exclusion of Article 12 is due to the fact that 1) the police member is deemed criminal not the main actor of crime; 2) extortion is deemed ordinary crime; 3) extorted items are returned by the police members committing extortion; 4) general court takes time to deliver ruling. Keywords: extortion, police, bidpropam